Chemical analysis of volatile oils in Eucalyptus species by GC mass - Jaafer ALtememmi, Noor; Jameel ALjudy , Neamat; Ahmed ALzubaid, Labeeb (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Essential oils have many possible applications and are thus commonly employed as a functional element. Hydrosols, byproducts of plant distillation, have been used in the food and cosmetics sectors as well as biological agriculture; yet, little is known about the volatile content of hydrosols. To determine the chemical content of the essential oils of Eucalyptus leaves. The yields of leaves essential oils from the hydrodistillation of Eucalyptus species were 0.6- 1% (based on fresh leaves). Gas chromatography-mass spectrometry (GC-MS) methods were employed for Oils found in the leaves of 20 types of Eucalyptus trees in Baghdad, Iraq. Terpenoids and alkaloids are abundant in both types of oils. The terpenoid contains mostly monoterpene hydrocarbons, sesquiterpenoids, and only six species contain the diterpenoid. Essential leaf oils exhibited greater activity, probably due to the higher p-cymene concentration in leaves. Eucalyptus constitutions contain high levels of terpene diversity, led by monoterpenes and sesquiterpenoids, with 17 out of 20 species containing alkaloids. Different types of constitutions demand different methods to use the species medically or commercially.